URBAN ARCHITECTURE AS A TRANSFORMATION OF IDENTITY : A Study Case from Pekanbaru City, Indonesia - Yohannes Firzal (Jurnal Koridor, 2018)
Identity of place can be changed and reconstructed. This is seen as capable of supporting dynamic changes in real life through the transformation of practices and the articulation of social relations. In this sense, the identity is affected by culture and cultural production, and is an unfixed, unfinished and varying process that affects both the place and society. By using a qualitative approach, this study investigates the influence of Malay culture in Pekanbaru city. The field data are grouped, analysed, and interpreted within an iterative process to expand understanding of the processes of reconstructing identity, and how the identity on the margins becomes an exclusive set of collective identities. Thus, this paper shows connections between the culture and identity of place which is identified through architecture and socioâ€cultural change in urban society.